Combined Effect of Inflammation and Hyperglycemia on Mild Cognitive Impairment and Associated Dietary Patterns in an Older Taiwanese Population - Fan, Yen-Chun; Chou, Chia-Chi; Bintoro, Bagas Suryo; Pan, Wen-Harn; Bai, Chyi-Huey (Frontiers in Nutrition, 2022)
Background Previous studies have demonstrated that C-reactive protein (CRP) and glycated hemoglobin (HbA1c) levels are independently associated with neurodegenerative diseases, which can be improved by altering dietary patterns. The purpose of this study was to investigate the combined effect of CRP and HbA1c, as well as the influence of dietary patterns, on dementia risk. Methods A cross-sectional study was conducted with 536 participants aged ≥65 years who were recruited from the Nutrition and Health Survey in Taiwan from 2014 to 2016. The high levels of inflammation and glycation were defined as CRP level >0.21 mg/dL and HbA1c level ≥6.50%, respectively. Mild cognitive impairment (MCI) was evaluated using the mini-mental state examination score. The dietary patterns associated with CRP and HbA1c levels were assessed using reduced rank regression. Multivariate logistic regression models of both complete and imputed datasets were performed. Results Participants with high levels of both CRP and HbA1c were associated with the highest odds ratio (OR) of MCI (adjusted OR [aOR]=3.52; 95% confidence interval [CI]=3.48, 3.56; P<0.001), followed by a high level of only HbA1c (aOR=1.73; P<0.001) and CRP (aOR=1.49; P<0.001). Using reduced rank regression, an inverse relationship of nuts and seeds with CRP and HbA1c was found (both factors loading < -0.2). Concerning the combined effect of tertiles among factor 1 and factor 2 analyzed by dietary patterns, group 1 with both T3 (high tertiles) was associated with the greatest odds ratio of MCI (aOR =4.38; 95% CI=4.34, 4.42; P<0.001) using multiple imputation. Conclusions The combination of high levels of inflammation and hyperglycemia was associated with an increased likelihood of MCI. Moreover, dietary patterns positively related to inflammation and hyperglycemia were associated with mild cognitive impairment, while eating nuts and seeds promoted better cognition.